Anodized nano-coating of copper material for thermal efficiency enhancement - Mahmood, M.H.; Maleque, Md. Abdul (The Mattingley Publishing Co., Inc., 2020)
This paper presents the effects of Nano-coating process parameters on the thermal efficiency enhancement of copper substrate material. A comparison experimental results of Nano copper oxide coating prepared in oxalate solution at various operating conditions with different porosities and grain sizes. The study evaluate the effects of the Nano coating on the enhancement of heat transfer of copper substrate. Effect of oxalate concentration on the grain size and porosity of coating was investigated at various operating conditions of temperature and agitation. The Nano copper oxide coatings were conducted at the ambient temperature and below, in range of oxalate concentration between 0.1 - 0.5M using linear sweep voltammetry (LSV) method. The coating was performed in Auto lab Potentiostat with scan rate 0.02 V/Sec. the coating’s characterization was done using Field Emission Scanning Electron Microscopy (FESEM). The thermal effects of the Nano anodized coating was evaluated according to the coating’s grain size and porosity, which formed at various oxalate concentrations. The result shows that Nano anodized coating improves the thermal efficiency of copper by 96.5 % as a result of the increment in the heat transfer surface area around 350 times.